1983
DOI: 10.1093/nar/11.5.1439
|View full text |Cite
|
Sign up to set email alerts
|

Base substitutions in the wobble position of the anticodon inhibit aminoacylation of E. colitRNAfMet by E. coli Met-tRNA synthetase

Abstract: Derivatives of E. coli tRNAfMet containing single base substitutions at the wobble position of the anticodon have been enzymatically synthesized in vitro. The procedure involves excision of the normal anticodon, CAU, by limited digestion of intact tRNAfMet with RNase A. RNA ligase is then used to join each of four trinucleotides, NAU, to the 5' half molecule and to subsequently link the 3' and modified 5' fragments to regenerate the anticodon loop. Synthesis of intact tRNAfMet containing the anticodon CAU by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
12
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…On the basis of the ratio of 32P to A2w, specific activities of 800-1,000 pmol/A2m unit are obtained. As noted previously (3), similar specific activities are obtained for equivalent amounts of intact tRNAfmet after electrophoresis and isolation from polyacrylamide gels due to contamination of small samples with nondialyzable, ethanol-precipitable UV-absorbing material from the gels. The 32p label incorporated during the synthesis has therefore been used to calculate the actual concentration-of each product for aminoacylation studies.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…On the basis of the ratio of 32P to A2w, specific activities of 800-1,000 pmol/A2m unit are obtained. As noted previously (3), similar specific activities are obtained for equivalent amounts of intact tRNAfmet after electrophoresis and isolation from polyacrylamide gels due to contamination of small samples with nondialyzable, ethanol-precipitable UV-absorbing material from the gels. The 32p label incorporated during the synthesis has therefore been used to calculate the actual concentration-of each product for aminoacylation studies.…”
supporting
confidence: 76%
“…These results focused our attention on the anticodon, the variable loop, and the acceptor stem of tRNAfMet for more detailed analysis of the structural requirements for protein-tRNA recognition. We have shown that the anticodon wobble base plays an essential role in this process (3,4 Synthesis of Oligonucleotides. The trinucleotides GpCpA and CpApU were synthesized by reaction of GpC with ADP and CpA with UDP, using polynucleotide phosphorylase as described by Thach and Doty (7).…”
mentioning
confidence: 99%
See 3 more Smart Citations